FINANCIAL RATIO ANALYSIS TO ASSESS THE PERFORMANCE OF THE COMPANY IN THE USE OF WORKING CAPITAL (Case Study on PT. Bentoel Internasional Investama, Tbk.) - Wiryana, Clara Shinta; Ratnawati, Kusuma (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
Each company has the same purpose in maintaining the viability of the company is to get the maximum benefit or profit. To achieve that purpose, sufficient working capital in order to carry out activities of daily company operations. The purpose of this study was to determine how the company's performance in the use of working capital in PT. Bentoel Internasional Investama, Tbk. measured activity ratios, profitability ratios, liquidity ratios. The analysis technique used is the analysis of financial statements using ratio analysis tool that includes activities activity ratio (Total Asset Turnover, Inventory Turnover, Working Capital Turnover, Receivables Turnover, Average Collection Period), the ratio of profitability (Return on Assets, Return on Equity), liquidity ratio (Current Ratio, Quick Ratio, Cash Ratio). The financial statements were analyzed from 2008 to 2011. From the analysis of the study found that PT. Bentoel Internasional Investama, Tbk. the activity ratio has increased and decreased from year to year, only the working capital turnover ratio which always showed an increase in each year. Judging from the ratio of profitability, the company experienced a decline in 2009 and a sharp increase in the ratio in 2010. When viewed from the liquidity ratios, the company showed a fairly good condition in the current ratio and the quick ratio, only the cash ratio has decreased from 2010 to 2011.Key words: Financial Ratio, Performance of the Company, Working Capital of PT. Bentoel Internasional Investama, Tbk.